Appropriateness of imaging decisions for low back pain presenting to the emergency department: A retrospective chart review study - Traeger, Adrian C.; Machado, Gustavo C; Bath, Sally; Tran, Martin; Roper, Lucinda; Oliveira, Crystian [UNESP]; Peek, Aimie; Coombs, Danielle; Hall, Amanda; Tcharkhedian, Elise; Maher, Chris G. (Oxford University Press (OUP), 2021)
Background: Imaging for low back pain is widely regarded as a target for efforts to reduce low-value care. Objective: We aimed to estimate the prevalence of the overuse and underuse of lumbar imaging in patients presenting with low back pain to the emergency department (ED). Methods: This was a retrospective chart review study of five public hospital EDs in Sydney, Australia, in 2019-20. We reviewed the clinical charts of consecutive adult patients who presented with a complaint of low back pain and extracted clinical features relevant to a decision to request lumbar imaging. We estimated the proportion of encounters where a decision to request lumbar imaging was inappropriate (overuse) or where a clinician did not request an appropriate and informative lumbar imaging test when indicated (underuse). Results: Six hundred and forty-nine patients presented with a complaint of low back pain, of which 158 (24.3%) were referred for imaging. Seventy-nine (12.2%) had a combination of features suggesting that lumbar imaging was indicated according to clinical guidelines. The prevalence of overuse and underuse of lumbar imaging was 8.8% (57 of 649 cases, 95% CI 6.8-11.2%) and 4.3% (28 of 649 cases, 95% CI 3.0-6.1%), respectively. Thirteen cases were classified as underuse because the patients were referred for uninformative imaging modalities (e.g. referred for radiography for suspected cauda equina syndrome). Conclusion: In this study of emergency care, there was evidence of not only overuse of lumbar imaging but also underuse through failure to request lumbar imaging when indicated or referral for an uninformative imaging modality. These three issues seem more important targets for quality improvement than solely focusing on overuse.
Keywords: diagnostic imaging; low back pain; medical overuse; quality improvement